HUBUNGAN DUKUNGAN KELUARGA DENGAN KEMANDIRIAN PASIEN GANGGUAN JIWA DI WILAYAH KERJA PUSKESMAS SIDOMULYO RAWAT INAP PEKANBARU - Deby Rayendra; Fathra Annis Nauli; Yufitriana Amir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Mental disorders are clinically significant syndromes or behavioral patterns that are directly related to distress (suffering) and cause disability (disability) in one or more functions of human life. Family support is the attitude, action and acceptance of the family towards family members who are supportive, always ready to provide help and assistance if needed. Independence is knowing how to manage time, learn and think independently, accompanied by the ability to take risks and solve problems. This study aims to determine how the relationship between family support and the independence of mental patients in the working area of the Sidomulyo Health Center Inpatient Pekanbaru with a quantitative research design that is descriptive of correlation with a cross sectional approach. The research sample was 43 respondents who were taken based on inclusion and exclusion criteria using purposive sampling technique. The measuring instrument used is a questionnaire sheet. The analysis used is univariate and bivariate analysis using Chi Square statistical test with an alpha value of 0.05 (5%). The results showed that the p value was 0.002, so there was a significant relationship between family support and the independence of mental patients in the work area of the Pekanbaru Inpatient Sidomulyo Health Center.Keywords: Family Support; Independence; Mental Disorder.